Microfabrication of a micron-scale microbial-domestication pod for in situ cultivation of marine bacteria. Issue 43 (3rd October 2022) - Wheatley, Sydney K.; Cartmell, Christopher; Madadian, Elias; Badr, Sara; Haltli, Bradley A.; Kerr, Russell G.; Ahmadi, Ali
Abstract : Through the hyphenation of microfabrication, microfluidics and microbiology, we report the development of a μMicrobial-Domestication Pod (μMD Pod) for in situ cultivation of bacteria. Abstract : Through the hyphenation of microfabrication, microfluidics and microbiology, we report the development of a μMicrobial-Domestication Pod (μMD Pod). This in situ cultivation device facilitates cell signaling from neighbouring species and interactions with environmental stimuli for marine bacterial growth to overcome current barriers faced by standard laboratory cultivation methods.